2015
DOI: 10.2989/20702620.2014.999304
|View full text |Cite
|
Sign up to set email alerts
|

A new screening method forGanoderma philippiitolerance in tropicalAcaciaspecies

Abstract: Red root rot disease caused by Ganoderma philippii is one of the most economically important diseases of tropicalAcacia species. Research on field control of the disease has to date focused on inoculum reduction, silviculture practices and application of biological control agents. Incorporation of tolerant genotypes, a key component of integrated disease management, has not been adequately explored because of a lack of reliable and quick screening protocols. Recently, we developed a more rapid method of screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Salah satu species utama untuk bahan baku pulp adalah A.mangium [2]- [4]. Pada tahun 2020 kebutuhan pulp diperkirakan mencapai 490 juta ton m 3 . Oleh karena itu banyak dilakukan perluasan lahan penanaman akasia termasuk dilahan-lahan marginal [2].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Salah satu species utama untuk bahan baku pulp adalah A.mangium [2]- [4]. Pada tahun 2020 kebutuhan pulp diperkirakan mencapai 490 juta ton m 3 . Oleh karena itu banyak dilakukan perluasan lahan penanaman akasia termasuk dilahan-lahan marginal [2].…”
Section: Pendahuluanunclassified
“…Penanaman pada hutan tanaman Industri yang kebanyakan monokultur tidak dapat dipisahkan dari musuh alami serta peningkatan serangan hama dan penyakit [6].. Serangan hama dan penyakit pada tanaman A. mangium telah banyak dilaporkan. Beberapa penyakit yang menyebabkan kematian dan kerugian cukup besar antara lain akasia di HTI Sumatera diserang busuk akar yang disebabkan oleh Ganoderma philippi [3], [7]. Kebun benih semai uji keturunan A. mangium di Wonogiri, Jawa Tengah juga dilaporkan terinfeksi busuk akar yang disebabkan oleh G. steyaertanum [8].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…In recent years, fungal diseases, such as Ganoderma and Ceratocystis, have caused significant death in tropical Acacia plantations in Indonesia. Recent research has enabled rapid screening of planting stock for variations in tolerance and/or susceptibility to G. philippi (Gafur et al 2015), while preliminary trials on resistance and tolerance to Ceratocystis has indicated that the development of resistant breeds will be challenging (Brawner et al 2015).…”
Section: The Focus On Smallholder and Community Forestrymentioning
confidence: 99%
“…The level of damage and incidence of this disease required development of effective management to secure sustainable production of forest plantations [15,16]. Incorporation of resistant genotypes [17,18] and use of biocontrol agents of microbial consortiums [19][20][21] are economically and environmentally feasible control measures to minimize the losses due to the disease. The biocontrol agents developed so far to manage root rot pathogens include Trichoderma, Gliocladium, Cerrena, Phlebiopsis, and some other white rot fungal species.…”
Section: Introductionmentioning
confidence: 99%